The flexibility gamble: challenges for mainstreaming flexible approaches to climate change adaptation. Issue 4 (4th July 2021) - Metzger, Jonathan; Carlsson Kanyama, Annika; Wikman-Svahn, Per; Mossberg Sonnek, Karin; Carstens, Christoffer; Wester, Misse; Wedebrand, Christoffer
ABSTRACT: Adaptive and flexible approaches based on implementing different measures as new information emerges have been proposed as a way of enabling robustness towards uncertain future climate change. However, the success of flexible approaches in practice depends on the stability of the relevant organizational landscapes. In this paper, we draw upon key insights from the institutional theories of organizations and research on public administration and climate adaptation in Sweden. We argue that potential organizational instabilities pose a substantial challenge for the mainstreaming of flexible approaches to climate adaptation. Given the unstable character of the relevant organizational landscape in a very stable country such as Sweden, it seems reasonable to also seriously doubt the capacity of the relevant authorities in less stable countries to carry out a great number of monitoring-intensive, and hence attention-demanding, adaptive governance processes over time. Based on our results we argue that it is perilous to simply assume that flexible approaches to climate adaptation will lead to greater robustness.